Dynamic Stiffness of Pediatric Prostheses During Rapid Loading. Issue 4 (October 2020) - Agnew, Sarah; Geil, Mark D.; Gharai, Mohammad H.
ABSTRACT: Introduction: Individuals with limb loss rely on the use of prostheses to maintain functional independence and ambulatory capabilities. Because of the relatively higher and more rapid loads imposed by active children upon lower-limb prosthetic components, it is essential to understand the response of pediatric prostheses to dynamic loading. The purpose of this study was to quantify the stiffness characteristics of four pediatric prosthetic feet under different drop heights and contact orientations. Materials and Methods: Single-leg drop-landing was simulated with four pediatric prosthetic feet (College Park: Truper; Össur: Cheetah Junior, Flex-Foot Junior, Vari-Flex Junior). Each device was dropped from two different heights at two different contact orientations (forefoot, midfoot). Results: Stiffness ranged from 586.3 N/cm to 10, 628.4 N/cm. The running-specific Cheetah Junior was the least stiff. All feet were stiffer for flatfoot contact, but the Cheetah was least sensitive to foot angle. The Flex-Foot Junior and Truper had the largest increases in stiffness for flatfoot contact. Stiffness was not significantly different across the two drop heights, although individual feet showed differing responses. Conclusions: Forefoot contact mitigates force transmission in landing. Overall, the feet exhibited a large range of force, deformation, and stiffness results, indicating the possibility of activity-specific individualized prescription.